A Cure for PAINS? A Novel Approach to Management of Proton-Associated Internal Nasal Valve Stenosis. Issue 3 (August 2020) - Flukes, Stephanie; Hanson, Martin; Bott, Matthew; Cohen, Marc A.
Acquired internal nasal stenosis as a result of radiotherapy to the sinonasal region can be highly distressing for patients and difficult to correct surgically. We describe our experience using a controlled radial expansion balloon to dilate the area of stenosis, followed by stenting to the region. We achieved excellent results in 3 patients using this technique, with improvement in subjective nasal airflow across 100% of stenoses and complete resolution in 83%. This technique offers a simple and low-morbidity option for the management of acquired anterior nasal stenosis and is of particular value in cases of irradiation, which has the potential for poor tissue healing.